Full-scale numerical simulation of hemodynamics based on left ventricular assist device - Gao, Xinyi; Xu, Zhike; Chen, Chenghan; Hao, Pengfei; He, Feng; Zhang, Xiwen (Frontiers in Physiology, 2023)
Ventricular assist devices (VADs) have been widely used and accepted to treat patients with end-stage heart failure. The role of VAD is to improve circulatory dysfunction or temporarily maintain the circulatory status of patients. In order to be closer to the medical practice, a full-scale model of the left ventricular coupled axial flow artificial heart was considered to study the effect of its hemodynamics on the aorta. Because whether LVAD itself was connected between the left ventricular apex and the ascending aorta by catheter in the loop was not very important for the analysis of simulation results, on the premise of ensuring the full-scale simulation, the simulation data of the import and export ends of LVAD were imported to simplify the model. In this paper, the hemodynamic parameters in the ascending aorta, such as blood flow velocity vector, wall shear stress (WSS) distribution, vorticity current intensity, vorticity flow generation etc have been calculated. The numerical conclusion of this study showed the vorticity intensity under LVAD was significantly higher than that under patients’ conditions and the overall condition is similar to that of a healthy ventricular spin, which can improve heart failure patients’ condition while minimizing other pitfalls. In addition, high velocity blood flow during left ventricular assist surgery is mainly concentrated near the lining of the descending aorta lumen. What’s more, the paper proposes to use Q criterion to determine the generation of vorticity flow. The Q criterion of LVAD is much higher than that of patients with heart failure, and the closer the LVAD is to the wall of the descending aorta, the greater the Q criterion is. All these are beneficial to the effectiveness of LVAD in the treatment of heart failure patients and provide clinical suggestions for the LVAD implantation in clinical practice.